A OBMEP como estratégias de reprodução da matemática acadêmica - Moura, Jefferson Bento de (2023)
This research aimed to analyze the Brazilian Mathematical Olympiad for Public Schools (OBMEP) as a mechanism for legitimizing and reproducing Academic Mathematics. The following research question was focused: to what extent can OBMEP be understood as a strategy for legitimizing and reproducing Mathematics and how are the distinctive relationships established by its agents in the field of Mathematics? For the analysis, we used Bourdieu's theory as a reference with the concepts of habitus, field, capital and social mobility and references of Mathematics Education. To constitute the research materials, we surveyed various documents, such as application regulations, annual management reports, studies on OBMEP, data collected from medalists available on the official OBMEP website and mapping of dissertations and theses produced in Brazil, having as object of research the OBMEP. In addition to the data and documents, we conducted two interviews. OBMEP as the object of this research is justified by its size and scope: the number of students enrolled and awarded; by the number of participating institutions; for the investment that exceeds that of other Olympics. Its study is also justified by the fact that it is a competition that is created and administered by the Institute of Pure and Applied Mathematics, that is, by mathematicians who are recognized for developing high-level research in mathematics and are not recognized in the field of research in the field of mathematics. math education. Based on a qualitative study, we investigated the expectations and possibility of social mobility of OBMEP medalists. The results show an expectation of social mobility and a search for social transformation. The sociological investigation, carried out from the design of the field of mathematics, allowed an understanding of OBMEP as a strategy of mathematicians to value and legitimize their way of doing and seeing mathematics, imposing this vision on schools.